Displacement of the Scholar? Participatory Action Research Under COVID-19 - Auerbach, Jeremy; Muñoz, Solange; Affiah, Uduak; Barrera de la Torre, Gerónimo; Börner, Susanne; Cho, Hyunji; Cofield, Rachael; DiEnno, Cara Marie; Graddy-Lovelace, Garrett; Klassen, Susanna; Limeberry, Veronica; Morse, Aimee; et al. (Frontiers in Sustainable Food Systems, 2022)
The impact of COVID-19 on conducting research is far-reaching, especially for those scholars working for or alongside communities. As the pandemic continues to create and exacerbate many of the issues that communities at the margins faced pre-pandemic, such as health disparities and access to resources, it also creates particular difficulties in collaborative, co-developed participatory research and scholar-activism. These forms of community engagement require the commitment of researchers to look beyond the purview of the racialized capitalist and neoliberal structures and institutions that tend to limit the scope of our research and engagement. Both the presence of the researcher within the community as well as deep community trust in the researcher is required in order to identify and prioritize local, often counter-hegemonic forms of knowledge production, resources, and support networks. The pandemic and similar conditions of crises has likely limited opportunities for building long-term, productive relationships of mutual trust and reciprocity needed for PAR while communities refocus on meeting basic needs. The pandemic has now not only exacerbated existing disparities and made the need for engaged, critical and co-creative partnerships even greater, it has also abruptly halted opportunities for partnerships to occur, and further constrained funds to support communities partnering with researchers. In this paper we highlight accomplishments and discuss the many challenges that arise as participatory action researchers are displaced from the field and classroom, such as funding obstacles and working remotely. An analysis of experiences of the displacement of the scholar exposes the conflicts of conducting PAR during crises within a state of academic capitalism. These experiences are drawn from our work conducting PAR during COVID-19 around the globe, both in urban and rural settings, and during different stages of engagement. From these findings the case is made for mutual learning from peer-experiences and institutional support for PAR. As future crises are expected, increased digital resources and infrastructure, academic flexibility and greater consideration of PAR, increased funding for PAR, and dedicated institutional support programs for PAR are needed.